(untitled) (Journal of Dhaka Medical College, 2024)
Introduction: Prevalence of endometriosis is 6-10% in reproductive-age females. Around 25-35% of infertile women may be affected by endometriosis. Modalities of treatment for infertile patients depends on the stage of the disease. It starts from ovulation inducing drug to advanced ART. The objective of this study was to assess the outcome of surgical treatment in infertile, endometriosis patients. Materials and Methods: It was an observational study, which was conducted at Reproductive Endocrinology and infertility Unit, Dhaka Medical College. Total 144 patients were included during July 2018 to July 2021, aged 20-40 yrs. All the demographic variables, clinical and sonographic findings, and hormonal assessment were done. Then, staging was done by clinical pelvic assessment, and ultrasonographic findings. Patients who had ovarian endometrioma, more than 4 cm, were selected for laparoscopic surgery. In patients whose endometrioma was less than 4 cm, or had no ovarian endometrioma, were selected for ovulation induction with or without prior GnRH agonist therapy. Further infertility management were planned according to ovarian reserve, tubal patency, and male factor. Result: Mean age of the patients were 28.30±4.95 yrs. 75.0% patients had primary infertility. Dysmenorrhea was the most common symptom (86.96%), followed by chronic pelvic pain (81.16%). Bilaterality of endometrioma was associated with decreased serum AMH. Laparoscopic surgery was the mainstay of treatment, Cystectomy was done in 58% patients. Conservative treatment was done in remaining patients. Fertility enhancing treatment was done by ovulation inducing drug -letrozole, GnRH agonist, followed by controlled ovarian stimulation and followed by IUI. IVF was advised for fertility management in 26patients (18.06%). Conclusion: Endometriosis is not only associated with decreased ovarian reserve but also responsible for diminished response to ovarian stimulation. So, it is a great challenge to obtain successful fertility treatment for this group of patients. J Dhaka Med Coll. 2023; 32(1) : 9-15